Dabigatran Level Before Reversal Can Predict Hemostatic Effectiveness of Idarucizumab in a Real-World Setting - Gendron, Nicolas; Chocron, Richard; Billoir, Paul; Brunier, Julien; Camoin-Jau, Laurence; Tuffigo, Marie; Faille, Dorothée; Teissandier, Dorian; Gay, Juliette; de Raucourt, Emmanuelle; Suner, Ludovic; Bonnet, Corentin; et al. (Frontiers in Medicine, 2020)
Abstract Background. Idarucizumab has been included in guidelines for the management of bleeding or surgical procedure in dabigatran-treated patients without need for biological monitoring. The aim of the study was to assess the prognostic value of dabigatran plasma level before reversal to test the hemostatic efficacy of idarucizumab. Secondary objectives were (i) to analyze plasma dabigatran level according to the risk of rebound (ii) to evaluate the incidence of post-reversal non-favorable clinical outcomes (including thromboembolism, bleeding, antithrombotic and death) and antithrombotic resumption. Methods and Results. This was an observational multicentric cohort study which included all French patients who required idarucizumab for dabigatran reversal. Between May 2016 and April 2019, 87 patients from 21 French centers were enrolled. Patients received idarucizumab for overt bleeding (n=61), urgent procedures (n=24) or overdose without bleeding (n=2). Among patients with major bleeding (n=57), treatment with idarucizumab was considered effective in 44 (77.2%) of them. Patients who did not achieve effective hemostasis after reversal had a significantly higher mean level of plasma dabigatran at baseline (524.5 ±386 versus 252.8 ng/mL ±235, p=0.033). Furthermore, patients who did not achieve effective hemostasis after reversal had less favorable outcomes during follow-up (46.2% versus 81.8%, p=0.027). ROC curve identified a cut-off of 264 ng/mL for dabigatran level at admission to be predictive of ineffective hemostasis. No plasma dabigatran rebound was observed after reversal in patients with dabigatran plasma level <264 ng/ml at baseline. Conclusion. This retrospective study shows that dabigatran level before reversal could predict hemostatic effectiveness and dabigatran plasma rebound after idarucizumab injection.